2008
DOI: 10.2337/dc07-0858
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Diabetes Management System Based on Practice Guidelines, Integrated Care, and Continuous Quality Management in a Federal State of Germany

Abstract: OBJECTIVE—The aim of this study was to evaluate the Saxon Diabetes Management Program (SDMP), which is based on integrated practice guidelines, shared care, and integrated quality management. The SDMP was implemented into diabetes contracts between health insurance providers, general practitioners (GPs), and diabetes specialized practitioners (DSPs) unified in the Saxon association of Statutory Health Insurance Physicians. RESEARCH DESIGN AND METHODS—The evaluation of the SDMP in Germany represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
7

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 21 publications
4
71
0
7
Order By: Relevance
“…Previous evaluations of the German DMP for type 2 diabetes show that this program curbs drug and hospital costs, may reduce mortality (Stock et al 2010;Miksch et al 2010), and improves the ongoing quality of diabetes care (Rothe et al 2008;Szecsenyi et al 2008). However, dealing with comorbidity is an enormous challenge in the German DMP for type 2 diabetes.…”
Section: Introductionmentioning
confidence: 97%
“…Previous evaluations of the German DMP for type 2 diabetes show that this program curbs drug and hospital costs, may reduce mortality (Stock et al 2010;Miksch et al 2010), and improves the ongoing quality of diabetes care (Rothe et al 2008;Szecsenyi et al 2008). However, dealing with comorbidity is an enormous challenge in the German DMP for type 2 diabetes.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, experience from the NHS QOF and similar incentive-based disease management programs in other countries underline the influence of financial incentives on the quality of medical documentation. For instance, in Germany, the Saxon Diabetes Management Program that compromised, inter alia, incentives for data documentation by GPs, reported an increase of completed data to 91-98% [37]. On the other hand, retrospective investigations in England have shown that an overall increase of the recorded quality of diabetes care had already existed in the pre-QOF period, just like in other countries and irrespective of the introduction of the pay-for-performance scheme in 2004 [28,38,39].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Scientific outcome evaluation indicators and measurement recommendations (e.g., body weight, waist circumference, HbA 1c and total energy intake) have been developed to monitor the effectiveness and efficiency of the programs [56]. Recent experience demonstrates that monitoring alone, as a function of quality management, is a driver for increasing the quality of intervention programs [57]. The CDC DPRP, as part of the National DPP, serves this monitoring function for diabetes prevention programs in the USA.…”
Section: Health Marketingmentioning
confidence: 99%